Formulation And Characterization Of Oro Dispersible Films Of Etoricoxib (ET-ODF) - Kumar Vishwakarma, Dhaneshwar; Verma, Navneet; Sahani, Vibhu (Journal of Neonatal Surgery, 2025)
Drug delivery by oral route is the very convenient, safe and economical. The goal of the current study is to develop oro-dispersible films of etoricoxibe to improve patient compliance and convenience for older and younger patients, ultimately leading to improved therapeutic efficacy, in comparison to typical solid oral dosage forms. Using varying concentrations of PVA, HPMC and maltodextrinealong with glycerin, sodium starch glycolate, and purified water, different batches of oro-dispersible films of etoricoxibe were prepared by the solvent casting method. The films were then assessed for appearance, weight variation, thickness, folding endurance, drug content, disintegration time, in vitro drug release and Analgesic Activity. The optimized formulation F4 (PVA, HPMC and maltodextrine) exhibited acceptable folding endurance (more than 25), least disintegration time (51±1.00 seconds), highest drug content (59±0.89) and highest drug release (98.84±0.12%) in 10 minutes. It can be concluded from the study that the Oro Dispersible Films of etrocoxibe, formulation F4 for sublingual administration can be an optimized formulation.